Consumo de oxigênio durante ciclismo na máxima fase estável de lactato sanguíneo até a exaustão: modelo contínuo vs. intermitente - Grossl, T.; Barbosa, L. F. [UNESP]; De Lucas, R. D.; Guglielmo, L. G.A. (Centro Andaluz de Medicina del Deporte, 2014)
Objective: The aim of this study was to analyse the accumulated oxygen uptake (VO2), as well the main-tained time (TMcg) at high levels during a maximal lactate steady state (MLSS) exercise, determined incontinuous (MLSScon) and intermittent (MLSSint) modes, until exhaustion.Method: Fourteen trained cyclists performed an incremental maximal testing; 2-5 continuous and 2-4intermittent constant workload trials, in order to identify the MLSSconand MLSSint, respectively; twotests until exhaustion (TTE) (continuous and intermittent) were conducted using their respective MLSSworkloads.Results: The continuous TTE was significantly lower than TTE at intermittent protocol (54.7 ± 10.9 vs.67.8 ± 14.3 min; p = 0.001). The VO2at target workload (VO2cg) was higher at intermittent exercise(p < 0.05), at both situations (MLSS and TTE). On the other hand, TMcg and the VO2accumulated in MLSSworkloads (VO2ACcg) were higher during continuous mode (p < 0.0001), at both situations. The total VO2accumulated (VO2ACt) was similar between intermittent and continuous cycling (MLSS: 104.7 ± 8.7 L vs.103.9 ± 41.1 L and TTE: 193.8 ± 41.1 L vs. 226.4 ± 53.0 L, respectively).Conclusion: When MLSS continuous and intermittent were performed with same duration or untilexhaustion, the VO2ACt was similar, although the TMcg and VO2ACcg were smaller during intermittentexercise.
Oxygen uptake during cycling at maximal lactate steady state to exhaustion:Continuous vs. intermittent model
Keywords: Aerobic capacity; Cycling; Physiological response; Submaximal performance